A 28-GHz hybrid corporate-series fed four-element patch antenna array with improved bandwidth for 5G millimetre-wave application - Zakariyya, Sikiru Olayinka; Gbadamosi, Muibat Asabi; Yeketi, Ayinla Ally; Sadiq, Bashir Olaniyi (Universiti Teknologi MARA, Sarawak, 2026)
In this study, a different approach was taken toward the design and performance assessment of a four-element patch antenna operating at 28 GHz in the millimetre-wave band, specifically tailored for next-generation 5G wireless communication applications. Implemented on a Rogers RT 5880 dielectric substrate known for its low loss characteristics, the antenna benefits from a substrate thickness of 0.5 mm and a relative dielectric constant (εᵣ) of 2.2. The antenna array employs a microstrip line feeding technique, ensuring efficient signal transmission and distribution across the elements. Evaluation of the single-element configuration at 28 GHz frequency reveals impressive characteristics, including a return loss of −26.3 dB, signifying excellent impedance matching. Additionally, the antenna achieves a gain of 7.75 dB, an outstanding Voltage Standing Wave Ratio (VSWR) of 1.10, and a bandwidth of 1.34 GHz. To further enhance these characteristics, the antenna was configured as a two-element and a four-element array. Compared with the single-element antenna, the two-element array at 28 GHz shows a greater gain of 9.88 dB and an improved bandwidth of 2.04 GHz, while the four-element array shows the greatest gain of 12.5 dB and an expanded bandwidth of 4.89 GHz at the intended frequency of 28 GHz. This demonstrates how antenna performance is enhanced by utilising array structures. The performance of the proposed antenna was validated through comparative analysis with similar 28 GHz array antenna designs. The results indicate that the proposed antenna outperforms existing designs in both gain and bandwidth. The proposed antenna enhances high-capacity 5G millimetre wave (mmWave) communication and supports digital infrastructure development in line with SDG 9: Industry, Innovation and Infrastructure.